IMPLEMENTASI KONSEP PEMBELAJARAN "ACTIVE LEARNING" SEBAGAI UP AYA UNTUK MENINGKATKAN KEAKTIFAN MAHASISWA DALAM PERKULIAHAN - Muhtadi, Ali (MAJALAH ILMIAH PEMBELAJARAN, 2009)
The teaching and learning activities in higher education nowadays have been dominated and focused on the application of exposition or expository learning strategy. In the exposition learning strategy, lesson materials are presented to the participants who have the ability to control their own materials. As a consequence, students are become quite passive since there is no initiative to participate in the lecturing and also because of the less conducive condition where students have to develop knowledge by themselves. Students are encouraged to ask questions, raise opinions, or discuss relevant issues. In order to improve the students’ learning activities in the classroom to become more dynamic, we can apply one alternative study using "active learning" approach. The implementation of this learning model can be developed into 8 procedures or phases that are: (1) orientation (2) group forming (3) teamwork assignment (4) exploration (5) presentation (6) checking students’ understanding and the student ’s mastery of learning materials (7) reflection and feedback, and (8) formative evaluation.